Optimum design of plates structures under random loadings - Alves,Elcio Cassimiro (2013)
Structural optimization problems involving static loading have been studied for some time and in a way these kinds of problems are widely encountered in literature, but problems involving dynamic loading still have few studies not to mention problems involving nondeterministic dynamic loading. This paper presents a formulation of the optimization problem of plates subjected to random loadings. For the modeling of the structure, it used the bending plate element AST6 that explicitly provides these matrices, and dynamic mass reduction and rigidity matrices were used to reduce the computational cost of the problem. . The solution was achieved using the Interior Point Method and the sensitivity analysis of mass, and for the structure's stiffness matrixes the semi-analytical method was used. Three examples are presented to demonstrate the reliability of the process. The first example is an isotropic plate and the other two are problems involving sandwich plates. In all examples, an improved design in respect to the initially proposed geometry was obtained.